Pengaruh Media Pop-Up Book Terhadap Hasil Belajar Sejarah Indonesia Kelas X SMA Negeri 6 Padang - Indah Monicha; Hera Hastuti (Jurusan Sejarah FIS UNP, 2020)
The aim of this research is to find out the effect of application of pop-up book media in Indonesian History Lessons in Class X toward learning outcomes of SMAN 6 Padang. In this study, the pop-up book is done by students because with direct involvement in the learning process then student will be more understanble and cognitve will increased. This research is quantitative which using experiment method. The sample was taken using cluster random sampling technique. The sample of this research was students from class “X MIPA 1” as control class and class “X MIPA 3” as exsperimental class. Data collecting by giving a pretest and post-test using objective questions as many as 20 questions. The data were analyzed by using normality test, homogeneity test and hypothesis test. The average value of the pre-test results of class “X MIPA 1” was 61.25 and the class “X MIPA 3” was 60.63. The average value of the post-test results of class “X MIPA 1” was 71.25 and the class “X MIPA 3” was 82.8. The data were analyzed quantitatively by using t-test with the help of SPSS 23. The t-test obtained the significance value (Sig. 2-tailed) was 0.000 < (smaller than) 0.05. It can be concluded that there is an effect of the Pop-up Book media in Indonesian History Lessons in Class X toward learning outcomes of SMAN 6 Padang.